The Epic Vantage-Point: Roman Historiographical Allusion Reconsidered - Elliott, Jackie (Histos, 2015)
This paper makes the case that Roman epic and Roman historiographical allusive practices are worth examining in light of each other, given the close relationship between the two genres and their common goal of offering their audiences access to the past. Ennius’ Annales will here serve as epic’s representative, despite its fragmentary state: the fact that the epic shares its subject-matter with and pre-dates most of the Roman historiographical tradition as we know it suggests that the poem may have had a significant role in setting the terms on which the two genres interacted at Rome; and what the first surviving generation of its readers, as principally represented by Cicero, have to say about the epic rather confirms that suggestion (§I). Points of contact between the genres on which the paper focuses are: extended repetition of passages recognisable from previous authors (§II); allusion that is contested among the speakers of a given text (§III); citation practices (§IV); and the recurrence of recognisable material stemming from the Annales in the historiographical tradition’s latter-day, when all sense of that material’s original context has been lost, along with its ability to generate new meaning (§V).